2017
DOI: 10.3201/eid2307.170019
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Hemagglutinating Encephalomyelitis Virus and Respiratory Disease in Exhibition Swine, Michigan, USA, 2015

Abstract: Acute outbreaks of respiratory disease in swine at agricultural fairs in Michigan, USA, in 2015 raised concern for potential human exposure to influenza A virus. Testing ruled out influenza A virus and identified porcine hemagglutinating encephalomyelitis virus as the cause of influenza-like illness in the affected swine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 9 publications
1
40
1
Order By: Relevance
“…Although PHEV infection has been endemic in different countries for decades and the primary route of PHEV infection is through upper and lower respiratory tracts, only few reports suggest an association of the virus with respiratory disease in swine (Cutlip and Mengeling, 1972). Recently, we have demonstrated that PHEV caused an influenza-like illness (ILI) in affected pigs and provided evidence for the role of PHEV as a respiratory pathogen (Lorbach et al, 2017). In that study, a significantly higher positive rate 38.7% (108 of 279 pigs) was observed in pigs at the Michigan fairs compared to 4.1% (23 of 560 pigs) in Indiana and Ohio, indicating the PHEV-associated epizootic behavior in the Michigan fairs (Lorbach et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Although PHEV infection has been endemic in different countries for decades and the primary route of PHEV infection is through upper and lower respiratory tracts, only few reports suggest an association of the virus with respiratory disease in swine (Cutlip and Mengeling, 1972). Recently, we have demonstrated that PHEV caused an influenza-like illness (ILI) in affected pigs and provided evidence for the role of PHEV as a respiratory pathogen (Lorbach et al, 2017). In that study, a significantly higher positive rate 38.7% (108 of 279 pigs) was observed in pigs at the Michigan fairs compared to 4.1% (23 of 560 pigs) in Indiana and Ohio, indicating the PHEV-associated epizootic behavior in the Michigan fairs (Lorbach et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
“…Recently, we have demonstrated that PHEV caused an influenza-like illness (ILI) in affected pigs and provided evidence for the role of PHEV as a respiratory pathogen (Lorbach et al, 2017). In that study, a significantly higher positive rate 38.7% (108 of 279 pigs) was observed in pigs at the Michigan fairs compared to 4.1% (23 of 560 pigs) in Indiana and Ohio, indicating the PHEV-associated epizootic behavior in the Michigan fairs (Lorbach et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations